326Flavonoid intake and ischemic stroke incidence in the Danish Diet, Cancer, and Health Cohort. (2nd September 2021) - Parmenter, Ben; Dalgaard, Frederik; Murray, Kevin; Cassidy, Aedin; Bondonno, Catherine P; Lewis, Joshua R; Croft, Kevin D; Kyrø, Cecilie; Gislason, Gunnar; Scalbert, Augustin; Tjønneland, Anne; Overvad, Kim; et al.
Abstract: Background: Flavonoid-rich foods may contribute to a lower risk of ischemic stroke through their anti-inflammatory, anti-atherogenic, and anti-thrombotic properties. We aimed to examine the relationship between flavonoid intake and ischemic stroke incidence in participants from the Danish Diet, Cancer, and Health study. Methods: In this prospective cohort study, 55, 169 Danish citizens without a prior ischemic stroke (median [IQR] age at enrolment of 56 [52 – 60] years), were followed for 21 [20 – 22] years. Baseline flavonoid intake was estimated from food frequency questionnaires using the Phenol-Explorer database. Incident cases of stroke were identified from Danish nation-wide public health registries. Associations between quintiles of flavonoid intake and incident ischemic stroke were assessed using Cox proportional hazard models adjusting for age, sex, BMI, smoking status, physical activity, alcohol intake, education, and income. Results: During follow-up, 4, 317 individuals experienced an ischemic stroke. Compared to participants in quintile one and after multivariable adjustments, those in quintile five for intake of total flavonoids, flavonols and oligo+polymers had a 12% [HR (95% CI): 0.88 (0.81, 0.96)], 10% [0.90 (0.82, 0.98)], and 18% [0.82 (0.75, 0.89)], lower risk of ischemic stroke incidence, respectively. Intake of flavan-3-ol monomers, anthocyanins, flavanones and flavones were not associated with incident ischemic stroke. Conclusions: A moderate habitual intake of flavonoids, in particular the flavonol and flavan-3-ol oligo+polymer subclasses, is associated with a lower risk of ischemic stroke. Key messages: Flavonoid rich foods appear protective against ischemic stroke.